Demographic and health scenario of tribal people in Rangamati Sadar Thana - Mullah, Muhammad Abu Shadeque; Parveen, Nabila; Ahshanullah, Mohammad (BRAC University, 2010)
In South East Asia, Bangladesh is a densely populated country with a well-off tribal presence. Around 58 tribes are living in different parts of the country. Bangladesh has 1.2 million tribal people, which is just above 1 percent of the total population. Whatever the inhabitants they diverge in their traditional social organization, marital customs, rites and rituals, food and other customs from the people of the rest of the country. This paper presents a short description of the demographic and health characteristics of the Tribal people of Rangamati Sadar Thana on the basis of data collected through a field survey. This paper also discovers that the tribal people are lagging behind the general population with respect to demographic, health, political and technological standings and still living with outdated lifestyle and principles.